Prognostic Factor of Soluble ST2 Serum on 90 Days-Major Cardiovascular Events in ST-Elevation Acute Myocardial Infarction Patients with Reperfusion Therapy - Pamrayogi Hutomo; Anggoro Budi Hartopo; Indah Sukmasari; Ira Puspitawati; Putrika Prastuti Ratna Gharini; Budi Yuli Setianto (ACI (Acta Cardiologia Indonesiana), 2017)
Background: Soluble ST2 (sST2) is released by strained myocardial. High baseline sST2 levels have been shown to be a predictor of mortality and heart failure in STEMI patients within 30 days and within 1 year, but its effect on medium-term events has not been widely investigated. Aims: To assess the prognostic factor of sST2 levels during admission with major cardiovascular events in the form of cardiovascular death and heart failure due to left ventricular dysfunction within 90 days of observation. Methods: A retrospective cohort study was conducted on STEMI patients with an onset of ≤ 24 hours undergoing reperfusion therapy from April 2014 - June 2015 in Dr. Sardjito General Hospital, Yogyakarta, Indonesia. The sST2 sample of venous blood was performed at admission. Primary outcomes for this analysis included cardiovascular death and congestive heart failure (CHF) through 90 days of follow-up. Assessment of major cardiovascular events was based on medical record data. Bivariate analysis were conducted on demographic and clinical factors related to sST2 and major cardiovascular events. A multivariate analysis was then conducted to determine the independent factors that influenced the emergence of major cardiovascular events. Results: Of the 107 patients who met the subject criteria, there were 33 (30.8%) subjects withmajor cardiovascular events and 74 subjects (69.2%) without major cardiovascular events in 90 days of observation. Of the 33 subjects with major cardiovascular events, there were 10 subjects (9.3%) died and 23 subjects (21.5%) with heart failure. The sST2 levels did not have a significant relationship with the incidence of mortality (p=0.617), heart failure (p=1.000), orboth combined (p = 1.000) in 90 days of observation. Conclusion: High serum sST2 levels during admission in STEMI patients who had undergonereperfusion therapy were not associated with increased incidence of major cardiovascular events (either the incidence of mortality or heart failure alone or both combined) in 90 days observation.